African societies facing global dynamics:Turbulences between external intervention, migration, and food insecurity. Research report - Schiefer, U.; Larcher Carvalho, A.; Dünnwald, S.; Bayan, L.; Jung, P. (2013)
INTRODUCTION This research report compiles information about the research conducted for the project: African societies facing global dynamics: Turbulences between external intervention, migration, and food insecurity (project Reference: PTDC/AFR/104597/2008). The project was financed by the Fundação para a Ciência e Tecnologia (FCT) and started in 2009 with the duration of 36 months. The host institution was the Centre for African Studies (now Centre for International Studies) at ISCTE-IUL with a number of partner organizations. The PI was Ulrich Schiefer. The project engaged a large number of researchers for a number of years who prepared articles, dissertations, organised conferences and made oral presentation at national and international conferences. Participating institutions ? Centro de Estudos Africanos (CEA/ISCTE), Portugal ? Centro de Estudos Africanos da Universidade do Porto (CEAUP), Portugal ? Instituto Nacional de Estudos e Pesquisas (INEP), Guinea-Bissau ? Universidade de Cabo Verde (Uni-CV), Cape Verde ? Groupe de Recherches sur les Migrations Maliennes Internes à L’Afrique (GREMI), Mali The objective of the project was to study the interactions between global dynamics and the dynamics of African societies, considering that these are complex and may lead to unforeseen effects and turbulences. Many actors try to change the internal dynamics of these societies through external interventions aiming at promoting development (these are mostly development aid interventions but also trade agreements and others). However, these have very often unexpected negative results, because linear causality models are assumed. The project tried to understand better the linkages between external and internal factors of change, how they work, how they affect each other mutually and what turbulences they can instigate. We do so by analysing what we called the “grey zone”, where both dynamics meet. In the grey zone, interactions are fuzzy and complex and neither well researched nor understood. Research at macro-level and at micro-level often comes to very different conclusions and levels of analysis are seldom linked. The zone of confluence of the various levels with its often invisible workings is neglected. It is therefore important to try to understand the complex interactions between global and internal dynamics in this grey zone. The research aimed at understanding better the flows in two main fields: food security and migration. Both fields are the target of several external interventions giving rise to significant planned and unforeseen consequences, creating tensions and turbulences and allowing the usually hidden parts of flows to become more visible. The project’s objectives were to analyse the interrelations between these two flows, their inter-relations with other important flows in African societies and their interaction with global dynamics. The results of the project included: 1. Development of a theoretical and methodological framework based on Case studies conducted in Mali, Senegal, Guinea-Bissau, São Tomé e Príncipe and Cape Verde. 2. Development of a research network on global dynamics and change in Africa societies 3. Discussion and communication of results. Below is presented a summary of the project’s outputs: ? Case studies and reports: Mali, Senegal, Guinea-Bissau, São Tomé & Príncipe, Cape Verde ? 4 Books o Peasants on the move o When food is short: household strategies sustaining livelihoods (in preparation) o A sociedade Joola-felupe face à (in)segurança alimentar: dinâmicas e estratégias (in preparation) o Food security and storage in Guinea-Bissau (in preparation) ? 11 Publications ? More than 30 communications in international meetings ? Organization of workshops, conferences with international guests ? Organizations of panels at 4 international African studies conferences CIEA7, ECAS 4, CIEA8, ECAS 5 ? Project sites • http://africadynamics.wordpress.com/ • http://foodsecurity.wordpress.com/ ? Advanced Training • 4 completed master thesis on the dynamics of change among the felupes of Guinea-Bissau • 1 master thesis on the dynamics of migration and their impact on Senegal and Cape Verde • 3 ongoing PhD thesis on power and change in Guinea-Bissau, remittances and migration The research report presented here gives an overview of the work conducted by the core team and presents a list of the outputs related to the project.